Information technology ed automazione del progetto (Strumenti per la didattica e la ricerca, 2002)
Here are collected the contributions presented during the conferences on "Information Technology and project automation" held at the Department of Engineering of Florence in 2000-01. Today the IT offer in the construction sector is very diversified and oriented towards specific support applications in the various phases of the project. The integration between these and the collaborative-working between the different subjects of the construction process thus appears to be an achievable goal, developing information systems and networks that tend to create shareable data platforms, inspired by the methods of process planning and integral design.